Digital interaction and student engagement in online English classes - Ridwan; Joaquim Correia Carvalho (Journal of Research in English Language Teaching and Linguistics, 2026)
This study addresses the role of digital interaction in enhancing student engagement within online English classes, a topic of growing importance as virtual learning environments increasingly replace traditional classrooms. Current literature recognizes various interactive tools, such as synchronous video calls and asynchronous discussion boards, as beneficial to learner motivation and participation; however, existing studies often examine these modalities in isolation and overlook the combined effects of synchronous and asynchronous interactions, as well as the influence of learner characteristics and engagement behaviors. This research aims to investigate multiple forms of digital interaction and their relationships with student engagement, considering contextual factors such as task complexity and learners’ familiarity with digital platforms. Employing a correlational design, the study involved 120 undergraduate students from three Indonesian universities enrolled in online English courses. Data were collected over a twelve-week semester through automated digital interaction logs capturing participation frequency and type across synchronous and asynchronous activities, alongside standardized engagement surveys administered thrice to measure behavioral, emotional, and cognitive engagement dimensions. The data analysis focused on correlating interaction patterns with engagement levels and assessing the combined effects of interaction types. Key findings indicate that synchronous interactions are more strongly linked to student engagement than asynchronous ones, with higher participation frequency correlating positively with engagement. Furthermore, the use of both interaction modes predicts engagement more effectively than either alone. Behavioral engagement was most directly influenced, while emotional and cognitive engagement evolved alongside active participation. The study implies that online English instruction should prioritize well-facilitated live sessions complemented by structured asynchronous activities to sustain overall engagement. Encouraging frequent and balanced participation enhances learners’ involvement, emotional connection, and deeper understanding, fostering more effective and holistic language learning experiences. These insights offer practical guidance for educators to design interactive, supportive, and technology-friendly online English courses that meet diverse learner needs.